Column-averaged dry-air mole fractions of CO2, CH4, and CO from direct sunlight measurements above the Western North Pacific during the MR21-01 campaign 2021 - Valentin Hanft; Ralph Kleinschek; Marvin Knapp; André Butz (PANGAEA, 2021)
Measurements of atmospheric column-averaged dry-air mole fractions of carbon dioxide (XCO2), methane (XCH4), and carbon monoxide (XCO) have been collected across the Western North Pacific ocean during the Measuring Mirai MR21-01 campaign in February to March 2021. We deployed a ship-going variant of the EM27/SUN Fourier Transform Spectrometer (FTS) on board the Japanese research vessel extquotesingleMirai extquotesingle which, during MR21-01, followed a circular route starting and ending at Shimizu Port, Japan to the Western North Pacific. Equipped with a custom-built fast solar tracker, the FTS operated in direct-sun view during the ship cruise reliably delivering solar absorption spectra in the shortwave infrared spectral range 4000 to 11000 1/cm. After filtering and bias correcting the dataset, we report on XCO2, XCH4, and XCO measurements for 22 days. The dataset has been adjusted to the TCCON (Total Carbon Column Observing Network) station in Karlsruhe, Germany, before the MR21-01 campaign through side-by-side measurements. During the campaign the precision for hourly means is found 0.332 ppm, 1.545 ppb and 1.041 ppb for XCO2, XCH4, and XCO, respectively.